An Observational Study on Echocardiographic Assessment of Left Ventricular Function Using Simpson’s and Global Longitudinal Strain Methods in Pre and Post Operative Coronary Bypassing Grafting Patient - R, Sabarivasan; Durgadevi, Durgadevi (Journal of Neonatal Surgery, 2025)
Background: Coronary artery disease is a major cardiac disorder among the current population. The main risk factors for coronary artery disease are diabetes mellitus, systemic hypertension, dyslipidemia, hypothyroidism, stress, alcohol consumption, and smoking affect the coronary arteries, which supply blood to the heart, making them stiff and rigid, resulting in loss of their flexibility. The free radicals from the risk factors cause damage to the Intimal layer of blood vessels, which leads to a series of inflammatory reactions, causing plaque formation(1). The plaque formation leads to decreased blood flow to the coronaries and causes ischemia to cardiac myocytes. It may progress to anaerobic metabolism of the myocyte that leads to cardiac myocyte injury, also known as Myocardial infarction(1). In patients affected by Myocardial infarction, the left ventricular function will be depressed as a result of the infarction. In echocardiography, various methods are used to assess the left ventricular function. Simpson’s and Global longitudinal strain were the most sensitive methods used to determine LV function(2). Objective: The aim of the study is to assess the Left ventricular function in patients undergoing bypass grafting by Simpson and GLS methods, and to conclude which of these two methods might be the most accurate to assess the LV function. Patients And Methods: A prospective observational study was done in 30 patients who presented to the cardiac OPD/Casualty with a clinical presentation of acute coronary syndrome, underwent coronary angiogram, and were further advised to undergo Coronary artery bypass grafting. In those patients, pre- and post-operative echocardiogram was done in order to evaluate LV function using GLS and Simpson’s method. Conclusion: The main use of bypass grafting in patients with coronary artery disease is to improve their LV Function. The purpose of this study is to promote that the current new echocardiography imaging techniques that enhance the accurate assessment of increased performance in LV Function in post bypass patients. In this contest, there are various number of methods which were derived to assess the LV Function. But in clinical aspect, the Simpson’s and Global longitudinal strain methods provides the accurate assessment of LV systolic function. In behalf of comparing both merits and demerits of Simpson’s and Global longitudinal strain methods, the LV Function assessed using the GLS is more reliable than the Simpson’s method(3).